Step-by-step Strategies for an Integrated Patient-Oriented Research: Lessons Learned from a Multicentered Study - Poitras, Marie-Eve; Godbout, Isabelle; T Vaillancourt, Vanessa; Débarges, Béatrice; Poirier, Annie; Prévost, Karina; Spence, Claude (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2020)
Introduction: The literature on Patient-Oriented Research (POR) and, more specifically, on the collaborative experience between research teams and patient partners (PPs), varies in the way it reports experiences. In Canada, since a few years, POR has been upgraded and literature now provides several guidelines and tools to support effective engagement of PPs in research. However, scientific literature most often presents elements from the researchers’ or from the PPs’ perspective, but rarely from both simultaneously. Objective: This paper objective is to enhance the current literature and provide examples of day-to-day pre, per, and post POR activities. Methods: Based on the 4 guiding principles of the Strategy for POR of the Canadian Institutes of Health Research, we present a step-by-step description of our POR strategies used during our research project. We also give concrete examples and tips shared by PPs and researchers. Discussion and conclusion: We favored 3 steps to engage positively our team in a POR approach. These steps led us to 3 main lessons. First, there is a necessity to adapt training on POR. Second, researchers must demonstrate open-mindedness and humility throughout the collaboration. Third, PPs’ recognition needs to be emphasized including a normalization of financial aspect. The reflections made in this article will help, hopefully, research teams to begin their patient-centered research process by building on the previous experiences of other teams, such as ours.